Will TLAC regulations fix the G-SIB too-big-to-fail problem? - Paul H. Kupiec (American Enterprise Institute (AEI), 2015)
The efficacy of the Financial Stability Board's proposed requirement for minimum "total loss absorbing capacity" (TLAC) at global systemically important banks (G-SIBs) is assessed using a stylized model of a bank holding company and an equilibrium asset pricing model to value financial claims. I identify a number of G-SIB strategies that satisfy minimum TLAC requirements but fail to reduce implicit safety net subsidies that accrue to G-SIB shareholders or increase the resources available to recapitalize a failing G-SIB subsidiary. To meet the FSB's stated goals, TLAC requirements must impose minimum TLAC at all subsidiaries and restrict how TLAC funds can be invested. An equivalent, but much simpler solution is to significantly increase regulatory capital requirements on systemically important bank subsidiaries.
Keywords: A; 330; TLAC total loss absorbing capacity]; G-SIBs [global systemically important banks]; bail-in capital; SPOE [single point of entry strategy]